1999
DOI: 10.1021/jp991634z
|View full text |Cite
|
Sign up to set email alerts
|

The Implication of the Connected Net Topology on the Morphology of β-Monoacid Triacylglycerol Crystals

Abstract: The crystal morphology of n.n.n TAGs, still the only triacylglycerol series of which the crystallographic structures have been elucidated, is predicted using a revised version of the Hartman-Perdok theory. In an earlier publication by Bennema et al. 1 the morphology was predicted on the basis of attachment energy. The platelike shape of the crystals was predicted well, but the indices for the top faces failed. Second, the experimentally observed crystals are much more elongated. In the present approach, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(70 citation statements)
references
References 20 publications
6
63
0
Order By: Relevance
“…In the case of the presence of a DOF phase, it appears that faces can have a very high growth rate and still be macroscopically¯at. Experimental examples of such growth behaviour were found for the (011) face of naphthalene (Grimbergen, Reedijk et al, 1998), the (110) faces of orthorhombic n-paraf®ns (Grimbergen, van Hoof et al, 1998), the top faces of triacylglyceride (fat) crystals (Hollander et al, 1999) and the (110) faces of lysozyme . In this paper, it is shown that the BFDH and attachment-energy predictions are not generally applicable as the predictive value seems to be very poor even for many practical crystal graphs, when compared with the results of a complete connected-net analysis and MC simulation data.…”
Section: Discussionmentioning
confidence: 98%
“…In the case of the presence of a DOF phase, it appears that faces can have a very high growth rate and still be macroscopically¯at. Experimental examples of such growth behaviour were found for the (011) face of naphthalene (Grimbergen, Reedijk et al, 1998), the (110) faces of orthorhombic n-paraf®ns (Grimbergen, van Hoof et al, 1998), the top faces of triacylglyceride (fat) crystals (Hollander et al, 1999) and the (110) faces of lysozyme . In this paper, it is shown that the BFDH and attachment-energy predictions are not generally applicable as the predictive value seems to be very poor even for many practical crystal graphs, when compared with the results of a complete connected-net analysis and MC simulation data.…”
Section: Discussionmentioning
confidence: 98%
“…The 16.16.16 single crystals appear in the spherulites as long flat faceted needles with aspect ratios up to 500 and the 10.12.10 crystals as even narrower needles having aspect ratios up to 1000. In a recent paper the morphology of b-monoacid triacylglycerol (TAG) crystals was treated on the basis of a detailed connected net analysis [9]. In this paper the morphology of the crystals of n.n.n TAGS, with n even, was studied using a two dimensional (2D)-nucleation mechanism, taking into account the edge energies involved for the creation of such nuclei on the various crystal faces.…”
Section: Triacylglycerol Crystal Morphologymentioning
confidence: 99%
“…To find all connected nets giving rise to the possible flat (F-) faces the crystal graph representing all growth units (TAG molecules) and their mutual bonds is needed. For a discussion on the relevant bonds in case of TAG crystals we refer to Hollander et al [9]. In that paper it was shown that in order to predict the correct morphology for the b-TAGS merely a limited number of bonds between the growth units has to be considered.…”
Section: Connected Net Analysismentioning
confidence: 99%
See 2 more Smart Citations